PENGARUH STRUKTUR MODAL, LIKUIDITAS , UKURAN PERUSAHAAN DAN UMUR PERUSAHAAN TERHADAP KINERJA KEUANGAN - Jane Jessica; Yustina Triyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
Financial Performance is an analysis conducted to see the extent to which a company has implemented by using financial implementation rules properly and correctly. One measure of a company's financial performance that is directly related to the company's goals in general is the profitability ratio using Return on Assets. The purpose of this study was to determine the effect of capital structure, liquidity, firm size and firm age on financial performance. The theory used in this study is agency theory. The object of this research is the food and beverage sub-sector companies listed on the Indonesia Stock Exchange (BEI) in 2018-2020. Researchers conducted descriptive statistical tests, pooling test, classical assumption test, F test, t test, and coefficient of determination. The data analysis technique used is multiple linear regression analysis. The conclusion of this study is that there is not enough evidence that liquidity and firm size have a positive effect on financial performance. While the age of the company there is sufficient evidence of a positive effect on financial performance. There is not enough evidence of capital structure to have a negative effect on financial performance.